2001
DOI: 10.1152/physiolgenomics.2001.6.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two susceptibility loci for vascular fragility in the Brown Norway rat

Abstract: A trait of vascular fragility, characterized by the formation of abrupt defects within the elastic laminae of the abdominal aorta, has been identified in Brown Norway (BN) rats. These lesions are greatly exacerbated in F(1) rats from a BN x New Zealand genetically hypertensive (GH) intercross, implying that the genetic background provided by the GH rat influences lesion severity. The F(2) progeny of the BN x GH intercross were used to identify susceptibility loci for the lesions as well as exacerbating loci. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
5
11
0
Order By: Relevance
“…Surprisingly, the average "wave grade" of the injured BN vessels was 2 (range 0 -6), compared with only 0.6 (range 0 -3) for the injured SHR vessels (P Ͻ 0.001). Together, these results are consistent with the thinner BN vessels (see below, Tables 2 and 3), which are also more fragile than the SHR vessels (11,23), being more easily distended than the more rigid SHR vessels. Thus the BN vessels had fewer injury-induced IEL breaks.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Surprisingly, the average "wave grade" of the injured BN vessels was 2 (range 0 -6), compared with only 0.6 (range 0 -3) for the injured SHR vessels (P Ͻ 0.001). Together, these results are consistent with the thinner BN vessels (see below, Tables 2 and 3), which are also more fragile than the SHR vessels (11,23), being more easily distended than the more rigid SHR vessels. Thus the BN vessels had fewer injury-induced IEL breaks.…”
Section: Resultssupporting
confidence: 84%
“…If this were the case, then the initial MA or MW of a given F 2 (SHR ϫ BN) vessel might have a direct bearing on the amount of injury transmitted to that vessel and, in turn, influence its postinjury NIH production. In support of this, the differing numbers of postinjury IEL "breaks" and "waves" between the BN and SHR parental strains also suggest that a genetic difference in vessel fragility and distensibility (11,23) may directly influence the postinjury responses of the vasculature. We are currently trying to determine whether or not these differences in postinjury vascular changes between the BN and SHR strains can be influenced by endothelial vasodilators.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, the vascular walls of BN rats have been reported to harbor several anomalies compared with other strains, including a high incidence of ruptures of the internal elastic lamina of large arteries and a decreased concentration of aortic elastin. 29 Moreover, internal elastic lamina ruptures have been linked to 2 QTLs on chromosomes 5 and 10 in a cross between BN and the New Zealand Genetically Hypertensive rat, 30 and the aortic elastin content has been linked to 2 QTLs on chromosome 2 and 1 QTL on chromosome 14 in a cross between BN and Louvain rats. 31 Although these 2 traits indicate that there is vascular fragility in BN rats, it is unknown whether they have an impact on PP.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding the BN rat, a significant but weak negative correlation was observed in the six other strains between aortic elastin content or elastin-to-collagen ratio and IEL rupture, suggesting that the aortic elastin deficit is, at the most, a minor contributory factor that may be permissive, but it certainly does not explain the very high levels of IEL rupture in the BN rat. Recent studies have identified QTLs for IEL rupture on chromosomes 5 and 10 (6,8), findings that may lead to identification of candidate genes involved in this phenotype.…”
Section: Discussionmentioning
confidence: 99%